Aspects of Pacemakers Functions and Interactions in Cardiac and Non-Cardiac Indications - Vonend, Oliver; Eckert, Siegfried (IntechOpen, 2011)
Outstanding steps forward were made in the last decades in terms of identification of endogenous pacemakers and the exploration of their controllability. New "artifical" devices were developed and are now able to do much more than solely pacemaking of the heart. In this book different aspects of pacemaker - functions and interactions, in various organ systems were examined. In addition, various areas of application and the potential side effects and complications of the devices were discussed.